The inhibition of Mpro, the primary protease of COVID-19, by Poria cocos and its active compounds: a network pharmacology and molecular docking study. Issue 20 (25th March 2021) - Wu, Zhimin; Chen, Xiaoxue; Ni, Weiju; Zhou, Danshui; Chai, Shanshan; Ye, Weile; Zhang, Zhengpu; Guo, Yuanqiang; Ren, Liping; Zeng, Yu
Abstract : The inhibition of Mpro, the primary protease of COVID-19, by Poria cocos . Abstract : Poria cocos is a traditional Chinese medicine (TCM) that can clear dampness, promote diuresis, and strengthen the spleen and stomach. Poria cocos has been detected in many TCM compounds that are used for COVID-19 intervention. However, the active ingredients and mechanisms associated with the effect of Poria cocos on COVID-19 remain unclear. In this paper, the active ingredients of Poria cocos, along with their potential targets related to COVID-19, were screened using TCMSP, GeneCards, and other databases, by means of network pharmacology. We then investigated the active components, potential targets, and interactions, that are associated with COVID-19 intervention. The primary protease of COVID-19, Mpro, is currently a key target in the design of potential inhibitors. Molecular docking techniques and molecular dynamics simulations demonstrated that the active components of Poria cocos could bind stably to the active site of Mpro with high levels of binding activity. Pachymic acid is based on a triterpene structure and was identified as the main component of Poria cocos ; its triterpene active component has low binding energy with Mpro. The pachymic acid of Mpro activity was further characterized and the IC50 was determined to be 18.607 μmol L −1 . Our results indicate that pachymic acid exhibits a certain inhibitory effect on the Mpro protease.